A new genus of Liocranidae (Arachnida: Araneae) from Tajikistan - Marusik Yuri M.; Fomichev Alexander A. (Pensoft Publishers, 2022)
A new genus, Platnick gen. n., with three new species, P. shablyai sp. n. (♂, type species), P. astana sp. n. (♀) and P. sanglok sp. n. (♀), are described from Tajikistan. The male of the type species has a unique pair of longitudinal ventral postgastral scuta. Females have such scuta also, but they are much shorter. The new genus is placed in Liocranidae Simon, 1897. A discussion on the subfamilies of Liocranidae and comments on the family-group names are provided.